Effect on nitrogen economy, productivity and energetics of wheat (Triticum aestivum) under double cropping systems - PADHI, A K; PARIDA, A K (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1994-96 to study the effect of rainy season (kharif) crops on the productivity,energetics and nitrogen economy of succeeding wheat (Triticum aestivum L. emend. Fiori & Paol.) under double cropping systems. Among the rainy season crops, redgram (Cajanus cajan L. Millsp, ) + blackgram (Phaseolus mungo L.) at 2:2 paired row ratio recorded the highest yield on wheat equivalent basis ( 2 210 kg/ha ), Wheat succeeding redgram + blackgram performed better with maximum grain yield (3695 kg/ha). With the highest quantity of total wheat equivalent yield (6 905. kg/ha ), net return (Rs 18 298/ha), return/rupee invested (Rs 2.02), production efficiency (25.6 kg/day/ha), energy output (189 851 MJ/ha), energy output: input ratio (7.92), energy-use efficiency (29 kg/100 MJ) and N-uptake (29.93 kg/ha) redgram + blackgramÂ  wheat sequence appeared to be economically and energetically viable sequence followed by redgram-wheat sequence in sandy loam soils. Application of 80 kg N/ha to wheat recorded maximum wheat yield (4 319 kg/ha), total wheat equivalent yield (6638 kg/ha), net return (Rs 12 551/ha), return/rupee invested (Rs 1.70), production efficiency (28.5 kg/day/ha), energy output: input ratio (7.91) and energy-use efficiency (26 kg/100 MJ). At the optimum production level of wheat after fallow (4 282.68 kg/ha) the highest quantity of 38.76 kg N/ha could be saved in wheat succeeding redgram + blackgram.